A LOGICAL FRAMEWORK APPROACH FOR SME'S TERM OF REFERENCE, BUDGET PLAN AND COOPERATIVE PROJECT - Putri, Dini Ajani; Hidayat, Muhammad Thariq; Kharisma, Bayu; Hadian, Yudha (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2020)
One of the most crucial stages in the new system of PP 17/2017 on Synchronization of National Development Planning and Budgeting is creating a comprehensive and accurate Terms of References (TOR) and budget plan, which define all aspects of how line ministries or stakeholders will conduct the priority project. Taking one example of priority projects of the Ministry of Cooperatives and SMEs, which is called Pusat Layanan Usaha Terpadu/ PLUT KUMKM, this study aims to identify how line ministry (the Ministry of Cooperatives and SMEs) describes its project and overall perceives the new system of planning and budgeting. Using logical framework approach, this study analyzes a number of documents such as TOR, budget plan, and government plan that related to PLUT KUMKM project. The result shows that the Ministry of Cooperatives and SMEs needs to improve the perception of the new system since the TOR and budget plan cannot fully describe the project comprehensively.